Early Postoperative Arrhythmias after Paediatric Cardiac Surgery - Hoque, Kazi Zahidul; Sultana, Akhand Tanzih; Mia, Mamun; Chowdhury, Masumul Gani; Hossein, Makbul (Delta Medical College Journal, 2018)
Background: The radical change in techniques in paediatric cardiac surgery has dramatically reduced the morbidity and mortality. The different varieties of arrhythmia that are frequently observed in postoperative period in our country are still not well documented. Objectives: To determine the incidence and risk factors of arrhythmia immediately after cardiac surgery in paediatric age group. Materials and method: It was a prospective study. A total of 100 paediatric patients (age <18 years) who underwent cardiac surgery at Dhaka Shishu Hospital between 2013 and 2016 were selected purposively Results: Out of 100 patients maximum 41% were from 13-72 months age group. The mean age was 49.73±37.17 months with range of 0.5-231 months, 58% patients were male and rest were female. Postoperatively 31% subjects were arrhythmic and of these the highest number of patients suffered from junctional ectopic tachycardia. Out of these 100 patients, 39% were diagnosed as VSD followed by TOF (35%). Among 31 arrhythmic patients 59.83%, 41.93% and 3.22% manifested onset of arrhythmia at 1st, 1st to 2nd and 2nd to 7th postoperative period respectively. In this study age, body weight, cyanosis, CPB time, postoperative acidosis, ventilation support days, hypertension on arrival in ICU as well as ICU stay days were recognized as significant risk factors (p <0.05). Conclusion: Proper and careful monitoring of younger patient with lower body weight undergoing corrective cardiac surgery with long cardiopulmonary bypass (CPB) time may reduce the episodes of post operative arrhythmia. These patients may require high inotropic support post operatively. So, medical prevention and early diagnosis as well as proper management may improve the operative outcome. Delta Med Col J. Jan 2018 6(1): 22-28